Taxonomic and biological notes on Cardiastethus affinis and C. pseudococci pseudococci (Hemiptera: Heteroptera: Anthocoridae) in India - Yamada, Kazutaka; Bindu, K.; Nasser, M. (Zootaxa, 2008)
Cardiastethus affinis and C. pseudococci pseudococci were recognized in Kerala State, southern India: the latter is recorded from India for the first time. It is found that Cardiastethus affinis is associated with Orthaga exvinacea (Lepidoptera: Pyralidae) and C. pseudococci pseudococci is associated with Opisina arenosella (Lepidoptera: Xylorictidae). Revised diagnoses and illustrations of both species are given. Biological notes for Indian species of Cardiastethus and a key to the three local species of the genus are provided.